3D-MiXD: 3D-printed X-ray-compatible microfluidic devices for rapid, low-consumption serial synchrotron crystallography data collection in flow. (2020) - Monteiro, Diana C. F.; Stetten, David von; Stohrer, Claudia; Sans, Marta; Pearson, Arwen R.; Santoni, Gianluca
No abstract available